Evidence of reversible bradycardia and arrhythmias caused by immunogenic proteins secreted by T. cruzi in isolated rat hearts. - Héctor O Rodríguez-Angulo; Jhoan Toro-Mendoza; Juan A Marques; Juan L Concepción; Rafael Bonfante-Cabarcas; Yoliver Higuerey; Luz E Thomas; Leandro Balzano-Nogueira; José R López; Alfredo Mijares (PLoS Neglected Tropical Diseases, 2015)
Rationale Chagas cardiomyopathy, caused by the protozoan Trypanosoma cruzi, is characterized by alterations in intracellular ion, heart failure and arrhythmias. Arrhythmias have been related to sudden death, even in asymptomatic patients, and their molecular mechanisms have not been fully elucidated. Objective The aim of this study is to demonstrate the effect of proteins secreted by T. cruzi on healthy, isolated beating rat heart model under a non-damage-inducing protocol. Methods and results We established a non-damage-inducing recirculation-reoxygenation model where ultrafiltrate fractions of conditioned medium control or conditioned infected medium were perfused at a standard flow rate and under partial oxygenation. Western blotting with chagasic patient serum was performed to determine the antigenicity of the conditioned infected medium fractions. We observed bradycardia, ventricular fibrillation and complete atrioventricular block in hearts during perfusion with >50 kDa conditioned infected culture medium. The preincubation of conditioned infected medium with chagasic serum abolished the bradycardia and arrhythmias. The proteins present in the conditioned infected culture medium of >50 kDa fractions were recognized by the chagasic patient sera associated with arrhythmias. Conclusions These results suggest that proteins secreted by T. cruzi are involved in Chagas disease arrhythmias and may be a potential biomarker in chagasic patients.